AL-WASHLIYAH EDUCATIONAL COUNCIL POLICY IN THE DEVELOPMENT OF MADRASAH ALIYAH CURRICULUM IN NORTH SUMATERA - Mursal Aziz; Syafaruddin Syafaruddin; Mesiono Mesiono (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Education policy is one of the determinants of an organization in determining the educational goals. Al-Washliyah is one of the largest Islamic organizations in North Sumatera that has many educational institutions whose role is to help to educate the community. A good educational managementthrough the strategic policies will produce the good graduates. The role of the Al-Washliyah Educational Council in making curriculum development policies for Madrasah Aliyah (Islamic Senior High School) in North Sumatera is very urgent. One of the determinants of the success of the objectives of Islamic education at the Al-Washliyah educational institutions is the policy of developing Madrasah AliyahAl-Washliyah curriculum taken by the Al-Washliyah Educational Council. The Al-Washliyah Educational Council policy in developing Islamic education curriculum was by establishing the implementation of the policies in the form of Decree. Among the strategic policies taken by the Al-Washliyah Educational Council were the Al Washliyah curriculum, Al-WashliyahEducationsl System (SPA), the Diniyah Curriculum and additionalcurriculum for Islamic Religion subject. The purpose of this study was to find out how the characteristics of the Al-Washliyah Educational Council policies in developing Madrasah Aliyah Curriculum in North Sumatera.